Islamic Education Perspective Prof. Dr. Dja'far Siddik, MA. - Ismail Ismail; Usiono Usiono; Azizah Hanum OK (Universitas Muhammadiyah Enrekang, 2024)
Studies related to Islamic educational thought in Indonesia are still very much focused on national Islamic intellectual figures and Islamic classical figures. This raises a problem, namely the very limited development of Islamic education studies in Indonesia. Therefore, it is necessary to study the thoughts on Islamic education from other Islamic intellectual figures, especially Muslim intellectual figures whose identities and specific thoughts are rarely highlighted or whose identities and specific thoughts have not yet been revealed. Therefore, this scientific study aims to examine in more depth the thoughts on Islamic education from the perspective of Prof. Dr. Dja'far Siddik, MA. This scientific study uses the Systematic Literature Review (SLR) method with PRISMA analysis. The results of the analysis state that in his perspective, Prof. Djas has a quite different perspective compared to the perspective of other Muslim intellectual figures regarding Islamic education. This can be seen from how he interprets Islamic education and the aims of Islamic education